Crystal structure and physical properties of 1-methyl-3-(carboxymethyl)benzimidazolium betaine·CuBr2 in crystal and water solution. (18th November 2016) - Czekański, Łukasz; Hoffmann, Stanisław K.; Barczyński, Piotr; Gąsowska, Anna; Bregier-Jarzębowska, Romualda; Zalewska, Alina; Goslar, Janina; Ratajczak-Sitarz, Małgorzata; Katrusiak, Andrzej
Abstract : Planar CuO2 Br2 complex exists in a triclinic unit cell. Single crystal EPR and MO-theory give electron spin density delocalization parameters. Abstract : A new Cu(ii ) carboxylate coordinating compound [1-methyl-3-carboxymethyl benzimidazolium betaine]2 CuBr2 was synthesized and crystallized. The crystal has the triclinic symmetry P 1̄, with unit cell dimensions a = 7.9693, b = 8.4129, c = 9.1302 Å, α = 68.058, β = 85.402 and γ = 71.258 deg. ( Z = 1), and molecules stacked along the a -axis. Cu(ii )-complexes are planar and four-coordinated with chromophore CuO2 Br2, where two oxygen atoms belong to the carboxylate groups of two betaines acting as unidentate ligands. The compound was characterized by two-dimensional 1 H and 13 C NMR spectroscopy for the determination of the correlation between protons of a ligand molecule. NMR spectra confirm the coordination of Cu(ii ) ions and allow identification of H(2) proton as easily detached in basic conditions. FT-IR spectra confirm the unidentate coordination of the betaine carboxylate group. UV-Vis spectra show three bands in d–d-transition region. Energies of these transitions were used in the interpretation of the EPR results. From powder and single crystal EPR measurements the g -factors were determined as g x = 2.072, g y = 2.030, g z = 2.241. A non-typical g -factor sequence is a consequence of the orbital mixing in the ground state of Cu(ii ) complex of D 2h symmetry. The g -factors were interpreted in terms of the Molecular Orbital (MO) theory which delivered the Cu(ii ) unpaired electron density delocalization onto the ligand molecules. A strong delocalization on betaine molecules via in-plane ground-state orbital was found and unexpectedly also via out-of plane orbital directed towards the non-coordinating oxygen of the betaine carboxylate group.